Pengaruh Identitas Visual, Reputasi Akademik dan Kualitas Pelayanan terhadap Tingkat Kepuasan Mahasiswa Unsoed - Alisa Tri Nawarini; Ekaningtyas Widyastuti; Sulistyandari Sulistyandari (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2020)
This research has the aims to analyze the effect of visual identity ,academic reputation and service quality on student satisfaction at Unsoed. This research is descriptive research with survey method by using questionnaire to collect the data. Research results show that visual identity, academic reputation and service quality has positive effects on student satisfaction. Based on research result, FEB should increase the way to maintaining their visual identity ,increasing their academic reputation and enhancing service quality to maintaining student satisfaction.